2020
DOI: 10.3390/nu12113513
|View full text |Cite
|
Sign up to set email alerts
|

Choline Plus Working Memory Training Improves Prenatal Alcohol-Induced Deficits in Cognitive Flexibility and Functional Connectivity in Adulthood in Rats

Abstract: Fetal alcohol spectrum disorder (FASD) is the leading known cause of intellectual disability, and may manifest as deficits in cognitive function, including working memory. Working memory capacity and accuracy increases during adolescence when neurons in the prefrontal cortex undergo refinement. Rats exposed to low doses of ethanol prenatally show deficits in working memory during adolescence, and in cognitive flexibility in young adulthood. The cholinergic system plays a crucial role in learning and memory pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…Betaine supplementation during embryonic ethanol exposure in an avian embryo model reduces malformation defects observed following ethanol alone (Karunamuni et al, 2017 ). Following PAE, choline supplementation and working memory training in adolescent rats sufficiently improve the cognitive flexibility and connectivity deficits measured in adulthood (Waddell et al, 2020 ). Choline supplementation as an intervention for women drinking during pregnancy has been minimally investigated.…”
Section: Light At the End Of The Tunnelmentioning
confidence: 99%
“…Betaine supplementation during embryonic ethanol exposure in an avian embryo model reduces malformation defects observed following ethanol alone (Karunamuni et al, 2017 ). Following PAE, choline supplementation and working memory training in adolescent rats sufficiently improve the cognitive flexibility and connectivity deficits measured in adulthood (Waddell et al, 2020 ). Choline supplementation as an intervention for women drinking during pregnancy has been minimally investigated.…”
Section: Light At the End Of The Tunnelmentioning
confidence: 99%
“…Females exposed to prenatal EtOH showed memory impairments during the 0-s ITI sessions, whereas males showed only transient impairments during the early stages of learning, as evidenced by longer path lengths and larger heading angles on the initial days of testing. Previous preclinical studies have also reported that prenatal alcohol exposure impairs spatial working memory ( Schambra et al, 2017 ; Lucia et al, 2019 ; Waddell et al, 2020 ; Gursky et al, 2021 ), even at low to moderate ethanol doses ( Schambra et al, 2017 ; Waddell et al, 2020 ) and across different gestational periods ( Schambra et al, 2017 ; Lucia et al, 2019 ; Waddell et al, 2020 ; Gursky et al, 2021 ). Similar working memory deficits have been reported in clinical populations ( Kodituwakku et al, 1995 ; Moore et al, 2021 ; Chetty-Mhlanga et al, 2022 ).…”
Section: Discussionmentioning
confidence: 87%
“…Prenatal alcohol exposure can lead to difficulties in efficiently encoding information (Lewis et al, 2021), which is associated with slower information processing and/or utilization of inefficient and ineffective memory strategies (Lewis et al, 2021). Similarly, preclinical research confirms that prenatal alcohol exposure leads to spatial learning (Schambra et al, 2017;Aglawe et al, 2021) and working memory deficits (Schambra et al, 2017;Waddell et al, 2020;Gursky et al, 2021), consistent with the vulnerability of the developing hippocampus, a brain region important for learning and memory (Fontaine et al, 2016;Mattson et al, 2019;Dodge et al, 2020), and the prefrontal cortex, a brain region important in executive functioning including working memory (Mattson et al, 2019;Waddell et al, 2020;Gursky et al, 2021).…”
Section: Introductionmentioning
confidence: 81%
“…Individuals with a history of PAE may have a decrease in both gray and white matter in the cerebrum and cerebellum, as well as a reduction in gray matter within other brain structures such as the amygdala, hippocampus, putamen, caudate, thalamus, and pallidum [ 13 ]. Additionally, functional magnetic resonance imaging (fMRI) can be employed to study the developmental patterns of brain growth and identify alterations in neuronal networks following PAE [ 14 ]. Heart rate variability (HRV), which is based on fluctuations in time intervals between successive heartbeats, is another valuable tool in providing information about the autonomic nervous system activity [ 15 ].…”
Section: Introductionmentioning
confidence: 99%